Food Security, Agricultural Efficiency and Regional Integration - Amelia L. Bello (Philippine Institute for Development Studies (PIDS), 2004)
Food security remains a major concern among the APEC member economies. A simple and crude exercise shows that the region collectively could supply each member economys demands for rice, maize and wheat. Thus, there is a potential role for enhanced intra-APEC agricultural trade to address food security issues. However, economies may be reluctant to abandon a policy of pursuing self-sufficiency because of political sensitivities and because of the uncertainties that trade is sometimes associated with. While tariffs and subsidies have been addressed, nontrade barriers such as sanitary and phyto-sanitary conditions are imposed on agricultural commodities. Hence, regional cooperation must also be pursued along other grounds such as institutional support and the dissemination of technological advancements. In addition, a collective definition of food security must be answered by the 21 member economies.
Keywords: 330; agriculture sector; regional integration; regional cooperation; agricultural efficiency; Ernährungssicherung; Landwirtschaft; Agraraußenhandel; Regionale Wirtschaftsintegration; APEC-Staaten